2019
DOI: 10.1042/ns20180134
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the mammalian nervous system: a primer for neuroscientists

Abstract: Autophagy refers to the lysosomal degradation of damaged or superfluous components and is essential for metabolic plasticity and tissue integrity. This evolutionarily conserved process is particularly vital to mammalian post-mitotic cells such as neurons, which face unique logistical challenges and must sustain homoeostasis over decades. Defective autophagy has pathophysiological importance, especially for human neurodegeneration. The present-day definition of autophagy broadly encompasses two distinct yet rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 195 publications
(196 reference statements)
0
18
0
Order By: Relevance
“…It is notable that one patient (71 years old) has developed late-onset dementia decline, yet further studies are warranted before this can be attributed to ATG7 deficiency. Despite this, mutations in several genes that participate at multiple steps of autophagy have been implicated in familial neurodegeneration (Menzies et al, 2017;Suomi & McWilliams, 2019). However, there is evidence that the contribution of selective autophagy proteins to neurodegeneration may extend beyond their involvement in selective mechanisms alone.…”
Section: Adult Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is notable that one patient (71 years old) has developed late-onset dementia decline, yet further studies are warranted before this can be attributed to ATG7 deficiency. Despite this, mutations in several genes that participate at multiple steps of autophagy have been implicated in familial neurodegeneration (Menzies et al, 2017;Suomi & McWilliams, 2019). However, there is evidence that the contribution of selective autophagy proteins to neurodegeneration may extend beyond their involvement in selective mechanisms alone.…”
Section: Adult Neurodegenerationmentioning
confidence: 99%
“…Neurodegeneration is characteristic of autophagy‐deficient mouse models, yet the relationship between defective autophagy and human neurodegeneration has been more challenging to reconcile (Suomi & McWilliams, 2019 ). Strong evidence supporting the pathological involvement of autophagy includes the presence of large p62/SQSTM1‐ and ubiquitin‐positive inclusions, hallmarks of autophagy deficiency, in AD, PD and ALS brain tissues (Kuusisto et al , 2001 ; Mizuno et al , 2006 ).…”
Section: Atg7 In Human Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, major knowledge on the defective autophagy in humans is urgent to successfully treat patients. The importance of preventive or therapeutic autophagy regulation in neurodegenerative diseases is still debated (Bar-Yosef et al, 2019;Maiuri and Kroemer, 2019;Park et al, 2020;Suomi and Mc Williams, 2020). Negrete-Hurtado et al (2020) reported in ATG5 KO mice brain, a non canonical role of ATG proteins and that lipidation machinery is not required for neuronal survival.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we hope this editorial will encourage you to read some of the excellent work being published in Neuronal Signaling [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Of course, we would welcome any pre-submission queries and look forward to receiving your manuscripts in the future.…”
mentioning
confidence: 90%